2008
DOI: 10.1098/rspb.2008.0305
|View full text |Cite
|
Sign up to set email alerts
|

Can prey exhibit threat-sensitive generalization of predator recognition? Extending the Predator Recognition Continuum Hypothesis

Abstract: Despite the importance of predator recognition in mediating predator-prey interactions, we know little about the specific characteristics that prey use to distinguish predators from non-predators. Recent experiments indicate that some prey who do not innately recognize specific predators as threats have the ability to display antipredator responses upon their first encounter with those predators if they are similar to predators that the prey has recently learned to recognize. The purpose of our present experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 26 publications
(45 reference statements)
4
75
0
Order By: Relevance
“…their conspecifics falling prey). These findings support the threat sensitive hypothesis according to which prey species assess and adjust their behavior in accordance with the predation risk (Helfman 1989;Ferrari et al 2008). …”
Section: Discussionsupporting
confidence: 72%
“…their conspecifics falling prey). These findings support the threat sensitive hypothesis according to which prey species assess and adjust their behavior in accordance with the predation risk (Helfman 1989;Ferrari et al 2008). …”
Section: Discussionsupporting
confidence: 72%
“…Ferrari et al (2008c) tested juvenile rainbow trout for additive responses to two different chemosensory cues. Trout exposed conspecific disturbance and chemical alarm cues combined responded in an additive fashion, supporting the sensory complement hypothesis.…”
Section: Sensory Complementation and Threat-sensitive Learningmentioning
confidence: 99%
“…Indeed, Ferrari et al (2008c) found that fathead minnows conditioned with a high concentration of alarm cue (high perceived risk) exhibited generalised learning of trout cues, while minnows conditioned with low concentrations of alarm cue (low perceived risk) did not. These results suggest that prey may generalise the recognition only to highly threatening species but not to those of lower perceived risks.…”
Section: Generalising Of Predator Cuesmentioning
confidence: 99%
See 2 more Smart Citations